Materi Pendidikan Akhlak Dalam Pemikiran Burhanul Islam Az-Zarnuji - Abdul Halim; Turmuzi Turmuzi; Tengku Muhmmad Hendra; Kamidan Kamidan; Hasrian Rudi Setiawan (Al-Ulum: Jurnal Pendidikan Islam, 2020)
Studying knowledge is an important process and an obligation for every Muslim. But in his journey it turned out that not all claimants of knowledge are able to master, understand let alone apply the knowledge being studied and obtained. The reasons are diverse, the most dominant one is the neglect of the morality of al-karimah in each of the prosecutors of knowledge. At least, with what was revealed by Burhanu al-islam az-zarnuzi's book. in the muqoddimah of his book ta'lim muta'allim: